2017
DOI: 10.21037/tau.2017.03.03
|View full text |Cite
|
Sign up to set email alerts
|

Genital pain: algorithm for management

Abstract: Chronic testicular pain although becoming very common in our patient population poses a challenge to the physician, the patient and his family. The pathogenesis of chronic orchialgia (CO) is not well understood. The objective of this paper is to review the current literature on chronic testicular pain and its management and to propose an algorithm for its treatment. Abstracts, original papers and review articles were reviewed during a literature search using words such as testicular pain, CO, and microsurgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Microsurgical denervation of the spermatic cord (MDSC) is a minimally invasive surgical procedure used to manage CSP after the failure of conservative treatments [ 36 , 37 ]. Multiple retrospective studies have examined the use of MDSC for CSP.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Microsurgical denervation of the spermatic cord (MDSC) is a minimally invasive surgical procedure used to manage CSP after the failure of conservative treatments [ 36 , 37 ]. Multiple retrospective studies have examined the use of MDSC for CSP.…”
Section: Reviewmentioning
confidence: 99%
“…An increasingly used surgical treatment is Botox injection [ 34 , 37 ] because the botulinum-A toxin has been shown to modulate the release of neuropeptides (substance P and calcitonin gene-related peptide) that inhibit neurogenic inflammation and chronic pain [ 35 ]. However, a randomised, double-blind, controlled trial by Dockray et al found no superiority of onabotulinumtoxinA plus a local anaesthetic compared to a local anaesthetic alone for the control of SCP pain.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Calixte et al 66 performed a retrospective review of 44 patients with failed MDSC who underwent Scrotox from July 2013–2016. One hundred units of Botox diluted in 10cc of saline were injected medial and lateral to the spermatic cord at the level of the external inguinal ring.…”
Section: Treatment Algorithm For Chronic Orchialgia or Chronic Scrotamentioning
confidence: 99%
“…Calixte et al 66 performed a retrospective review of 82 patients who underwent TRAAD from June 2009 to April 2019. Selection criteria were as follows: chronic groin pain (>3 months), failed standard pain management treatments (including MDSC), patients who have persistent pain after orchiectomy and negative urologic workup.…”
Section: Treatment Algorithm For Chronic Orchialgia or Chronic Scrotamentioning
confidence: 99%